Comparison of Cricothyroid Membrane Puncture Anesthesia and Topical Anesthesia for Awake Fiberoptic Intubation: A Double-Blinded Randomized Controlled Trial - Wang, Shaocheng; Hu, Chaoli; Zhang, Tingting; Zhao, Xuan; Li, Cheng (Frontiers in Medicine, 2021)
Background: Awake fiberoptic intubation (AFOI) is commonly used for patients with a difficult airway. The purpose of this study was to evaluate the efficacy of cricothyroid membrane puncture anesthesia and topical anesthesia during AFOI. Methods: Seventy patients (American Society of Anesthesiologists score I-III) with anticipated difficult airways scheduled for non-emergency surgery with AFOI were randomly slated to receive cricothyroid membrane puncture anesthesia (n=35) or topical anesthesia (n=35). Each group received dexmedetomidine at a dose of 1.0 μg/kg and sufentanil at a dose of 0.2 μg/kg over 10 min for conscious sedation before intubation. The endoscopy intubation, post-intubation condition, and endoscopy tolerance as scored by the anesthetists were observed. The operator satisfaction regarding the procedure and the patient’s satisfaction 24 h after surgery were recorded as well. We recorded the success rate of the first intubation, intubation time, and hemodynamic changes during the procedure as well as the adverse events. Results: Better intubation scores, operator satisfaction, and patient satisfaction were observed in the cricothyroid membrane puncture anesthesia group than in the topical anesthesia group (P<0.05). The intubation time in the cricothyroid membrane puncture anesthesia group was less than that in the topical anesthesia group (P<0.05). There were no significant differences in the patient tolerance scores, success rate of the first intubation, hemodynamic changes, and adverse events between both groups. Conclusions: Compared with topical anesthesia, cricothyroid membrane puncture anesthesia provided better intubation conditions and less intubation time with greater patient and operator satisfaction during endoscopic intubation.